A method to achieve spectral beam combining based on a novel symmetric grating - Fan, Xinmin; Zhang, Jianxin; Li, Sensen; Li, Shun; Wang, Yan; Du, Fei; Huang, Xiaodong; Li, Yingde; Zhang, Lujun; Wang, Chunyan (Frontiers in Physics, 2022)
A symmetric grating is proposed to obtain higher output power in spectral beam combining by increasing the number of lasers and spectral utilization. The grating allows laser beams to be incident from both sides of the grating normal to achieve coaxial beam combining, the number of beams and the combined output power are doubled compared with the traditional grating under the same spectral line-width. The grating is designed with the central wavelength of 4.65μm, and the calculation results show that this grating is indeed very suitable for spectral beam combining, especially for the light waves in the range 4.55μm to 4.71μm, where the diffraction efficiency is high (over 80%) and their incident angles vary considerably. Finally, we further propose a circular grating based on the symmetric gratings to achieve the same frequency spectral beam combining, which is no longer necessary for each beam has to be broad spectrum. This study is very meaningful in some application fields and will further enrich the research of spectral beam combining.